Kontribusi Kemampuan Guru Melaksanakan Pembelajaran terhadap Hasil Belajar Persamaan Kuadrat pada Siswa SMA Negeri 1 Pangkal Pinang - Haholongan Simanjuntak (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
This research aims are to determine: 1) the contribution of teacher competencies; and 2) trends in students learning outcomes and students perception on learning quadratic equations. The population in this research comprises of all students in class X with a stratified sampling of 61 people taken randomly. The study uses two kinds of instruments, which consist of an instrument to collect data of learning outcomes in quadratic equation (Y) and an instrument to collect data of teacher education competencies (X) that are captured with a Likert scale of 30 questions. The result of the research concludes: 1) teachers education competencies contribute 49% to the quadratic equation learning outcome of students at SMA Negeri 1 Pangkalpinang; 2) students learning outcomes in quadratic equation are classified as adequate and good; 3) students evaluation on teachers ability to carry out the education process is relatively good. The research implicates that it is necessary to have a good coordination between the Education Ministry, LPMP and P4TK to improve mathematic teachers competencies by conducting courses/ seminars/workshops on pedagogical skills, mastery of teaching materials and instructional media, as well as the ability to select and use the right teaching methods. ABSTRAK Penelitian ini bertujuan untuk mengetahui: 1) kontribusi kemampuan guru, dan 2) kecenderungan hasil belajar siswa SMA Negeri 1 Pangkalpinang. Populasi penelitian meliputi seluruh peserta didik kelas X yang terdiri atas 4 kelas dan diambil secara acak dua kelas sebagai sampel berjumlah 61 siswa. Studi ini menggunakan dua jenis instrumen, yaitu instrumen untuk menjaring data hasil belajar matematika persamaan kuadrat (Y) dan instrumen untuk menjaring data kemampuan guru melaksanakan pembelajaran (X). Data kemampuan guru (X) dijaring dengan skala Likert yang instrumennya disusun sesuai dengan kisi-kisi terdiri atas 30 soal. Data hasil belajar matematika siswa (Y) dijaring dengan tes pilihan ganda. Hasil uji hipotesis menunjukkan bahwa terdapat kontribusi sumbangan kemampuan sebesar 49% dalam melaksanakan pembelajaran terhadap hasil belajar persamaan kuadrat pada siswa kelas X SMA Negeri 1 Pangkalpinang. Hasil uji kecenderungan variabel X dan Y menunjukkan bahwa kemampuan guru melaksanakan pembelajaran ditinjau dari persepsi siswa tergolong cukup baik dan hasil belajar matematika tergolong dalam kategori cukup dan baik.